Mortality in systemic lupus erythematosus in the United Kingdom 1999-2012 - Rees, Frances; Doherty, Michael; Grainge, Matthew J.; Lanyon, Peter; Davenport, Graham; Zhang, Weiya (Oxford University Press, 2016)
OBJECTIVES: To estimate the mortality associated with SLE during the period 1999-2012 by age, gender and region; and to ascertain the cause of death for people with SLE.